VD_FINDINFO HC / 2010 / 589 vom 20. Oktober 2010 - VD Tribunal cantonal (2010)
OBLIGATION D'ENTRETIEN, ACTION EN MODIFICATION, MINIMUM VITAL | 278 al. 2 CC, 286 al. 2 CC, 287 CC, 451 ch. 3 CPC, 452 al. 2 CPC